A nationwide evaluation of deceased donor kidney transplantation indicates detrimental consequences of early graft loss - de Kok, MJ; Schaapherder, AF; Mensink, JW; de Vries, AP; Reinders, ME; Konijn, C; Bemelman, FJ; van de Wetering, J; van Zuilen, AD; Christiaans, MH; Baas, MC; Nurmohamed, AS; et al. (Elsevier, 2020)
Early graft loss (EGL) is a feared outcome of kidney transplantation. Consequently, kidneys with an anticipated risk of EGL are declined for transplantation. In the most favorable scenario, with optimal use of available donor kidneys, the donor pool size is balanced by the risk of EGL, with a tradeoff dictated by the consequences of EGL. To gauge the consequence of EGL we systematically evaluated its impact in an observational study that included all 10,307 deceased-donor kidney transplantations performed in The Netherlands between 1990 and 2018. Incidence of EGL, defined as graft loss within 90 days, in primary transplantation was 8.2% (699/8,511). The main causes were graft rejection (30%), primary nonfunction (25%), and thrombosis or infarction (20%). EGL profoundly impacted short- and long-term patient survival (adjusted hazard ratio; 95% confidence interval: 8.2; 5.1-13.2 and 1.7; 1.3-2.1, respectively). Of the EGL recipients who survived 90 days after transplantation (617/699) only 440 of the 617 were relisted for re-transplantation. Of those relisted, only 298 were ultimately re-transplanted leading to an actual re-transplantation rate of 43%. Noticeably, re-transplantation was associated with a doubled incidence of EGL, but similar long-term graft survival (adjusted hazard ratio 1.1; 0.6-1.8). Thus, EGL after kidney transplantation is a medical catastrophe with high mortality rates, low relisting rates, and increased risk of recurrent EGL following re-transplantation. This implies that detrimental outcomes also involve convergence of risk factors in recipients with EGL. The 8.2% incidence of EGL minimally impacted population mortality, indicating this incidence is acceptable.